Comparison of low-order aerodynamic models and RANS CFD for full scale 3D vertical axis wind turbines - Delafin, Pierre-Luc; Nishino, Takafumi; Athanasios, Kolios; Lin, Wang (Elsevier, 2017)
A Double Multiple Streamtube model, a free-wake vortex model (both widely used for vertical axis wind turbine design) and RANS CFD simulations are used in this work to predict the performance of the 17 m Vertical Axis Wind Turbine, field tested by Sandia National Laboratories. The three-dimensional, full scale calculations are compared with the experiments in terms of power coefficient, power and instantaneous turbine torque to assess the validity of each model. Additionally, the two aerodynamic models and RANS CFD are compared to each other in terms of thrust and lateral force. The two models and CFD agree well with the experiments at the turbine optimal tip speed ratio. However, away from the optimal tip speed ratio, the streamtube model significantly deviates from the experimental data and from the other numerical models. RANS CFD gives a good agreement with the experiments, slightly underestimating the power coefficient at every tip speed ratio tested. The vortex model proves to be a useful tool with a better accuracy than the streamtube model and a much lower computational cost compared to RANS CFD.
Keywords: Double multiple streamtube; Free-wake vortex; 3D Computational Fluid Dynamics; Darrieus turbine; Instantaneous torque